ANALYSIS OF THE USE OF ARTIFICIAL INTELLIGENCE TECHNOLOGY IN PAI LEARNING AT SMPN 3 WONOSOBO - Navida Latifa naja; Maryono Maryono; Fatiatun Fatiatun (Alphateach (Jurnal Profesi Kependidikan dan Keguruan), 2026)
The development of 21st-century technology has brought significant changes to the world of education, including in Islamic Religious Education learning. However, the use of Artificial Intelligence technology in Islamic Religious Education learning is still not optimal and has not been systematically integrated. This study aims to analyze the use of Artificial Intelligence technology in Islamic Religious Education learning at SMPN 3 Wonosobo. This study uses a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. Data analysis is carried out through the stages of data reduction, data presentation, and conclusion. The results show that the use of Artificial Intelligence technology in Islamic Religious Education learning at SMPN 3 Wonosobo is quite developed, although it is still in the development stage. Artificial Intelligence is used by students to search for materials, answer questions, and create summaries, thereby increasing the effectiveness of learning and student learning independence. From the teacher's perspective, the use of Artificial Intelligence has been quite good in compiling teaching materials, creating questions, and planning lessons. However, the use of Artificial Intelligence has not been formally integrated into learning tools. In addition, there are several obstacles, such as limited student facilities, technical constraints, and lack of training for teachers. Therefore, facilities and training are needed to optimize the use of Artificial Intelligence technology in Islamic Religious Education learning.